2022
DOI: 10.1021/acs.jpcc.1c10612
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Light-Emitting Mechanism of Multifunctional Thermally Activated Delayed Fluorescence Molecules

Abstract: Multifunctional thermally activated delayed fluorescence (TADF) molecules have recently attracted great attention. The light-emitting mechanisms of the TADF molecule PTZ-AQ with aggregation-induced emission (AIE) and mechanochromic luminescence (MCL) in three different aggregation states are studied using the combined quantum mechanics and molecular mechanics (QM/MM) method as well as the thermal vibration correlation function method. It is found that different aggregation patterns would induce different inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…To gain a deep insight into the optical behaviors of the BY1, density functional theory (DFT) calculation was carried out at the B3LYP/6-311++G (d, 2p) level in the Gaussian 09 suite of programs [ 34 ]. The highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) were investigated by Multiwfn [ 35 ] and VMD software [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…To gain a deep insight into the optical behaviors of the BY1, density functional theory (DFT) calculation was carried out at the B3LYP/6-311++G (d, 2p) level in the Gaussian 09 suite of programs [ 34 ]. The highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) were investigated by Multiwfn [ 35 ] and VMD software [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the SOC constants between S 1 and T 4 for [DCF-MPYM-2H] 2− with three conformers are 12.90 cm −1 , 5.65 cm −1 and 12.09 cm −1 , respectively, which are larger than that of the TADF molecule previously reported. 54–58 According to the relationship, we can deduce that the RISC rate between T 4 and S 1 is relatively large, which is favorable for the conversion from triplet states to singlet states. The product [DCF-MPYM-2H] 2− is in the form of divalent anions, which causes stronger electromagnetic interactions as a result of electron motion around the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…[38] For the surrounding molecules, the universal force field (UFF) which sustains major elements 103301-2 is applied, which has also been proven reliable. [39,40] In the optimization process, the central molecule is completely released, while other molecules are locked. In our study, the ONIOM model of (R)-lmNBd (as shown in Fig.…”
Section: Theoretical Methods and Calculation Detailsmentioning
confidence: 99%